Relationship between method of anastomosis and anastomotic failure after right hemicolectomy and ileo‐caecal resection: an international snapshot audit. (2nd August 2017) - ,
Abstract: Aim: The anastomosis technique used following right‐sided colonic resection is widely variable and may affect patient outcome. This study aimed to assess the association between leak and anastomosis technique (stapled vs handsewn). Method: This was a prospective, multicentre, international audit including patients undergoing elective or emergency right hemicolectomy or ileo‐caecal resection operations over a 2‐month period in early 2015. The primary outcome measure was the presence of anastomotic leak within 30 days of surgery, determined using a prespecified definition. Mixed effects logistic regression models were used to assess the association between leak and anastomosis method, adjusting for patient, disease and operative cofactors, with centre included as a random‐effect variable. Results: This study included 3208 patients, of whom 78.4% ( n  = 2515) underwent surgery for malignancy and 11.7% ( n  = 375) underwent surgery for Crohn's disease. An anastomosis was performed in 94.8% ( n  = 3041) of patients, which was handsewn in 38.9% ( n  = 1183) and stapled in 61.1% ( n  = 1858). Patients undergoing handsewn anastomosis were more likely to be emergency admissions (20.5% handsewn vs 12.9% stapled) and to undergo open surgery (54.7% handsewn vs 36.6% stapled). The overall anastomotic leak rate was 8.1% (245/3041), which was similar following handsewn (7.4%) and stapled (8.5%) techniques ( P  = 0.3). After adjustment for cofactors, the odds of a leak were higher for stapled anastomosis (adjusted OR = 1.43; 95% CI: 1.04–1.95; P  = 0.03). Conclusion: Despite being used in lower‐risk patients, stapled anastomosis was associated with an increased anastomotic leak rate in this observational study. Further research is needed to define patient groups in whom a stapled anastomosis is safe.